1994
DOI: 10.1200/jco.1994.12.8.1572
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of high-dose and low-dose intravenous interleukin-2 for the therapy of metastatic renal cell carcinoma: an interim report.

Abstract: Low-dose intravenous bolus IL-2 represents an effective regimen for the treatment of metastatic RCC, with preliminary results comparable to those observed with high-dose IL-2. Low-dose IL-2 can be administered with significantly fewer complications, reduced use of vasopressor support, and fewer admissions to an intensive care unit (ICU).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(51 citation statements)
references
References 13 publications
1
49
0
1
Order By: Relevance
“…Overall response rates of renal cell cancer to IL-2 remain low (15-25%) with a complete remission rate of 5-10%. 45,46 Yet the dramatic response in a few patients where all other therapy has failed has established IL-2 as the standard therapy for this disease. Studies using IL-2 for ALL appear less encouraging.…”
Section: Resultsmentioning
confidence: 99%
“…Overall response rates of renal cell cancer to IL-2 remain low (15-25%) with a complete remission rate of 5-10%. 45,46 Yet the dramatic response in a few patients where all other therapy has failed has established IL-2 as the standard therapy for this disease. Studies using IL-2 for ALL appear less encouraging.…”
Section: Resultsmentioning
confidence: 99%
“…Posteriormente otros estudios reuniendo un total de 256 pacientes de varios centros confirmaron los resultados de Yang 25 .…”
Section: Actas Urológicas Españolasunclassified
“…19,20 However, a phase III study of the Cytokine Working Group found that treatment with high-dose IL-2 demonstrated a significantly higher objective response rate than did treatment with low-dose IL-2/interferon. 21 Conventional treatment options are summarized in Table 1.…”
Section: Therapy and Survivalmentioning
confidence: 99%